Instrument Kompetensi Tenaga Pendidik Dan Kependidikan Dalam Penyusunan Kurikulum - Taufan Adi Prayitno (Journal on Education, 2024)
The aim of this research is to analyze the Competency Instrument for Educators and Education Personnel in Curriculum Preparation in Educational Institutions in the Indonesian Navy. The research method used in this research is qualitative research. The results of the research are to gain a comprehensive understanding of the competencies of teaching and educational staff required in preparing the Indonesian Navy Education curriculum. By adopting a qualitative approach, researchers can explore the context and complexity involved in developing these competencies in greater depth. This approach allows researchers to look beyond data and numbers, but also to understand the backgrounds, motivations and experiences that influence the thoughts and actions of educators and educational staff. Thus, this research not only aims to identify specific educational needs, but also to present rich and contextual insights into how these competencies can be developed and applied in the Indonesian Navy educational environment.